Regulasi Naming and Shaming dalam Akuntansi Modern: Transparansi, Etika, dan Kepercayaan Publik - Alya Zalfa Adelina; Mukhtaruddin . (GLOBAL SCIENTS PUBLISHER, 2026)
Contemporary accounting regulation increasingly relies on naming and shaming as a transparency-based enforcement mechanism to enhance accountability and public trust. Despite its growing use, the ethical implications of public disclosure for professional judgment and regulatory legitimacy remain underexplored. This study examines naming and shaming as an ethical governance instrument in modern accounting regulation. Using a qualitative normative–conceptual approach, the study analyses prior literature through an integrated framework combining professional judgment theory, stakeholder theory, and normative ethical perspectives. The findings indicate that naming and shaming is not a valueneutral regulatory tool; its ethical effectiveness depends on proportionality, procedural fairness, and contextual implementation. While public disclosure may enhance transparency and stakeholder confidence, poorly designed reputational sanctions risk distorting professional judgment and encouraging defensive compliance. This study contributes an ethically grounded assessment of transparency-based enforcement and offers guidance for regulators and accounting professionals seeking to balance accountability, fairness, and public trust.